INVESTIGATION INTO ADVANCED AIR TRANSPORTATION NETWORK OF RUSSIAN FEDERATION - A. U. Udzhukhu; L. P. Titorenko (Научный вестник МГТУ ГА)
An approach allowing one to predict the development of air-route network is proposed. It proceeds from the principle of increasing the accessibility of points of destination, that is to make available for passengers non-stop flights or flights with one transit landing in case of the largest number of routes. With comparative analysis of possible variants of extending the structure of air-route network, it is reasonable to take into account a generalized time parameter and a number of alternative routes for passenger delivery from departure point to point of destination.